The Anti-inflammatory Effects of HMGB1 Blockades in a Mouse Model of Cutaneous Vasculitis - Wang, Jin; Fu, Lixin; Yang, Hao; Cao, Kai; Sun, Qiaomei; Chen, Tao (Frontiers in Immunology, 2020)
In our previous study, we have found the increased serum levels of HMGB1 in patients with Henoch– Schonlein purpura (HSP), allergic vasculitis (AV) and urticarial vasculitis (UV)and altered HMGB1 distribution in lesional skin in patients with HSP. HMGB1 play a pro-inflammatory role in the pathogenesis of HSP. To further investigated the role of HMGB1 in the pathogenic mechanism of vasculitis, we investigated the anti-inflammatory effects of HMGB1 blockade (including anti-HMGB1 mAb and glycyrrhizin) in a mouse model of cutaneous reverse passive Arthus (RPA) reaction. A total of Thirty-six balb/c mice were randomly divided into four groups: control group, IC model group, HMGB1 monoclonal antibody(anti-HMGB1-mAb) group and Glycyrrhizin group, with nine mice in each group. Cutaneous RPA reaction mouse model was established by injection of OVA antibody and OVA antigen. Mice of anti-HMGB1-mAb) group and Glycyrrhizin group were pre-treated with anti-HMGB1 mAb or glycyrrhizin respectively before the RPA reaction. Our results indicated that HMGB1 blockades (anti-HMGB1 mAb and glycyrrhizin) obviously extenuated the severity of vasculitis skin damage and improved the histological evolvement of inflammatory cells infiltration, vascular fibroid necrosis and vasodilation in Cutaneous RPA reaction mouse model. In addition, HMGB1 blockades reduced the infiltration of neutrophils, DCs and T cells and decreased the mRNA expression of IL-6 and CCL5 in skin lesions of Cutaneous RPA reaction mouse model. We suggest that HMGB1 blockade may represent a new direction for the treatment of Cutaneous vasculitis.